Computer and thinking - Lockwood, Victor; British Broadcasting Corporation. Television Service (Milton Keynes : Open University)
Discusses the relations between conputer and human thinking in psychology context
Converted into VHS 1/2 in. and U-matic
Title from title screen
filem AS122.06.DS261 filem 10
Film editor, Peter Elliot ; graphic, Haydon Yong ; executive producer, Michael Philps
Keywords: Thought and thinking; Computer-assisted instruction